2020
DOI: 10.3390/catal10060602
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Pyrolysis of Tetra Pak over Acidic Catalysts

Abstract: The thermal and catalytic pyrolysis of two kinds of Tetra Pak waste (TP-1 and TP-2) over three different acidic catalysts—HZSM-5(SiO2/Al2O3, 30), HBeta (38), and Al-MCM-41(20)—were investigated in this study. Tetra Pak (TP) wastes consist of composite material comprising kraft paper, polyethylene (PE) film, and aluminum foil. Thermal decomposition behaviors during the pyrolysis of TPs were monitored using a thermogravimetric (TG) analyzer and tandem micro reactor-gas chromatography/mass spectrometry (TMR-GC/MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…For example, at 800 W there was a wax yield production of about 1 wt.% in the absence of catalyst, but no wax was generated when catalyst was added. This is similar to Siddiqui's suggestion that catalyst was added to decrease wax formation (Siddiqui et al, 2020). Furthermore, the gas yield increased from 73 wt.% in the absence of catalyst to 78 wt.% at 500°C catalyst temperature.…”
Section: The Effect Of Ct On the Product Distribution Of Mwpsupporting
confidence: 87%
See 1 more Smart Citation
“…For example, at 800 W there was a wax yield production of about 1 wt.% in the absence of catalyst, but no wax was generated when catalyst was added. This is similar to Siddiqui's suggestion that catalyst was added to decrease wax formation (Siddiqui et al, 2020). Furthermore, the gas yield increased from 73 wt.% in the absence of catalyst to 78 wt.% at 500°C catalyst temperature.…”
Section: The Effect Of Ct On the Product Distribution Of Mwpsupporting
confidence: 87%
“…After that, the cellulose inside the paper layer decomposed at a temperature of 200°C to 400°C (Korkmaz et al, 2009). Meanwhile, the LDPE content of TW began to decompose at 400°C (Siddiqui et al, 2020). Furthermore, the temperature decreased because the capacity of the material used to increase the temperature had decreased (Motasemi and Afzal, 2013).…”
Section: Temperature and Mass Profilementioning
confidence: 99%
“…Pyrolysis and gasification can produce bio-oil by breaking the chains of large organic molecules at high temperature without oxygen [8]. However, the operating temperature is very high, usually in the range of 400-900°C, which would consume a lot of energy [9,10]. In addition, as the waste Tetra Pak is usually mixed with food scraps, such as milk, noodles, and other food debris with high moisture content, it would need more energy during the drying process of feed.…”
Section: Introductionmentioning
confidence: 99%
“…Siddiqui et al. found that the presence of catalyst HZSM‐5 promoted the generation of aromatic hydrocarbons via thermal cracking of TPW [16] . Co‐pyrolysis of TPW and waste motor oil was carried out by Tekin et al.…”
Section: Introductionmentioning
confidence: 99%